2022
DOI: 10.3390/ijerph19084531
|View full text |Cite
|
Sign up to set email alerts
|

Use of Artificial Neural Networks as a Predictive Tool of Dissolved Oxygen Present in Surface Water Discharged in the Coastal Lagoon of the Mar Menor (Murcia, Spain)

Abstract: The Mar Menor is a Mediterranean coastal saltwater lagoon (Murcia, Spain) that represents a unique ecosystem of vital importance for the area, from both an economic and ecological point of view. During the last decades, the intense agricultural activity has caused episodes of eutrophication due to the contribution of inorganic nutrients, especially nitrates. For this reason, it is important to control the quality of the water discharged into the Mar Menor lagoon, which can be performed through the measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…It is powerful and can be connected to other tools. This application showed a good results in previous studies [21,26].…”
Section: Development Of Mathematical Modelssupporting
confidence: 75%
“…It is powerful and can be connected to other tools. This application showed a good results in previous studies [21,26].…”
Section: Development Of Mathematical Modelssupporting
confidence: 75%
“…When studying the distribution of the world's TTW according to confrontation risk (Figure 2), the results of the investigation showed that 8 TTW areas are under a high confrontation risk (average score 5.1-6.0), 23 Currently, the highest confrontation risk among the TTW areas worldwide is in the Psou River mouth shared by the Russian Federation and, de jure, Georgia, although de facto, a breakaway region of Abkhazia controls the southern part of the Psou River mouth (Table 3). Russia has recognized and protects the independence of Abkhazia.…”
Section: Ttw Areas In the World Under High Confrontation Riskmentioning
confidence: 99%
“…The ever-increasing attention paid by researchers from diverse research fields to TW is primarily related to the inclusion of TW into the regulations imposed by the WFD on the EU Member States with regard to a good ecological status, its criteria, and its indicators [15]. The majority of papers on these issues have been published by authors from Mediterranean countries, i.e., Italy [16][17][18], Greece [19][20][21], and Spain [22][23][24] in particular. The investigated and assessed good ecological status indicators range from invertebrates [25][26][27] to fish [28][29][30] and aquatic macrophytes [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…In [10] the article objective is to forecast the dissolved oxygen (DO) in the water dumped into this lagoon. Additonally, a multiple linear regression (MLR) based back-propagation neural network (BPNN) methods are used for theoretical analysis.…”
Section: Standards Benchmarkmentioning
confidence: 99%